Design and development of ring-on-ring jig for biaxial strength testing of brittle ceramic composite materials: ZrB2-30wt-%SiB6. (19th May 2019) - Carrasco-Pena, Alejandro; Jordan, Ryan; Dieguez, Jessica; Coronado-Rodríguez, Arturo; Ozdemir, Veli B.; Kwok, Kawai; Orlovskaya, Nina; Vazquez-Molina, Demetrius A.; Uribe-Romo, Fernando J.; Bolon, Amy; Radovic, Miladin; Grasso, Salvatore; et al.
ABSTRACT: The strength of brittle ceramic materials is typically tested using simple uniaxial compression or by three- or four-point bending techniques. While these methods provide reliable results, they do not depict a realistic characterisation of the load-bearing capacity of structural materials, and a method that involves the application of multiaxial stress is required, such as the ring-on-ring biaxial flexural strength test. In this paper, an in-house ring-on-ring fixture was developed and validated by comparing the experimental and simulated biaxial strength tests of a model ZrB2 -30wt-%SiB6 ceramic composite. A description of the simulated finite element analysis is provided, and the stress field acting on the sample with maximum principal stress located at the surface under tension at the centre of the ceramic disk is shown.